Animated education resources (AEdoR) on Dato’ Bahaman for form two history subject / Muhamad Firdaus Hj Omar - Hj Omar, Muhamad Firdaus (2018)
History subject in school is often viewed as difficult subject by students. In year 2013, history has been made a core subject in Malaysian secondary schools and a compulsory subject to pass for Sijil Pelajaran Malaysia (SPM) Examination. This increases the challenges for the teachers to prepare good learning materials to teach and capture student’s interests. With the advances of information communication technology, especially in the field of interactive multimedia, teaching and learning opportunities has become more accessible and interesting. In this research, an animated historical topic was designed and developed to enhance the secondary student’s understanding of a historical topic on Dato’ Bahaman. This Animated Educational Resources or also known as AEdoR, was designed and developed based on a historical figure, in history topic for form two (2). This animated movie is 15 minutes in duration and it captures the essence of the content for the topic. Using a preliminary multiple case study approach through a design and developmental research, six (6) experts in the areas of history education, animation and instructional design participated in the design and development process. Sixty (60) secondary school students also viewed the animation and gave feedback to evaluate the effectiveness of learning history through animation. The studies conducted shown that AEdoR was able to enhance the teaching and learning of history through an animated multimedia and thus increases student’s interest to learn about Malaysian history. The researcher hoped to develop more related topics through AEdoR as a complete animated educational resource on Malaysian History.